A 640 × 640 ISFET array for detecting cell metabolism. (1st February 2023) - Yang, Ling; Huang, Yizheng; Song, Zhigang; Tan, Manqing; Yu, Yude; Li, Zhao
Abstract: Ion sensitive field effect transistor (ISFET) devices are highly accurate, convenient, fast and low-cost in the detection of ions and biological macromolecules, such as DNA molecules, antibodies, enzymatic substrates and cellular metabolites. For high-throughput cell metabolism detection, we successfully designed a very large-scale biomedical sensing application specific integrated circuit (ASIC) with a 640 × 640 ISFET array. The circuit design is highly integrated by compressing the size of a pixel to 7.4 × 7.4 μ m 2 and arranging the layout of even and odd columns in an interdigital pattern to maximize the utilization of space. The chip can operate at a speed of 2.083M pixels/s and the dynamic process of the fluid flow on the surface of the array was monitored through ion imaging. The pH sensitivity is 33 ± 4 mV/pH and the drift rate is 0.06 mV/min after 5 h, indicating the stability and robustness of the chip. Moreover, the chip was applied to monitor pH changes in CaSki cells metabolism, with pH shifting from 8.04 to 7.40 on average. This platform has the potential for continuous and parallel monitoring of cell metabolism in single-cell culture arrays.